SK4 calcium-activated potassium channels activated by sympathetic nerves enhances atrial fibrillation vulnerability in a canine model of acute stroke - Yang, Mei (Heliyon, 2020)
BACKGROUND: New-onset atrial fibrillation (AF) is common in patients with acute stroke (AS). Studies have shown that intermediate-conductance calcium-activated potassium channel channels (SK4) play an important role in cardiomyocyte automaticity. The aim of this study was to investigate the effects of SK4 on AF vulnerability in dogs with AS. EXPERIMENTAL: Eighteen dogs were randomly divided into a control group, AS group and left stellate ganglion ablation (LSGA) group. In the control group, dogs received craniotomy without right middle cerebral artery occlusion (MCAO). AS dogs were established using a cerebral ischemic model with right MCAO. LSGA dogs underwent MCAO, and LSGA was performed. RESULTS: Three days later, the dispersion of the effective refractory period (dERP) and AF vulnerability in the AS group were significantly increased compared with those in the control group and LSGA group. However, no significant difference in dERP and AF vulnerability was found between the control group and the LSGA group. The SK4 inhibitor (TRAM-34) completely inhibited the inducibility of AF in AS dogs. SK4 expression and levels of noradrenaline (NE), β1-AR, p38 and c-Fos in the atrium were higher in the AS dogs than in the control group or LSGA group. However, no significant difference in SK4 expression or levels of NE, β1-AR, p38 and c-Fos in the left atrium was observed between the control group and LSGA group. CONCLUSION: SK4 plays a key role in AF vulnerability in a canine model with AS. The effects of LSGA on AF vulnerability were associated with the p38 signaling pathways.